2021
DOI: 10.1017/s0033291721002671
|View full text |Cite
|
Sign up to set email alerts
|

Regular recreational Cannabis users exhibit altered neural oscillatory dynamics during attention reorientation

Abstract: Background Cannabis is the most widely used illicit drug in the United States and is often associated with changes in attention function, which may ultimately impact numerous other cognitive faculties (e.g. memory, executive function). Importantly, despite the increasing rates of cannabis use and widespread legalization in the United States, the neural mechanisms underlying attentional dysfunction in chronic users are poorly understood. Methods We used magnetoencephalography (MEG) and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 80 publications
6
15
1
Order By: Relevance
“…Finally, we also found that the association between the strength of spontaneous baseline activity and neural oscillations in the same spectral band was stronger in the dlPFC of cannabis users relative to nonusers, which may indicate that cannabis users are better able to compensate through increased oscillatory strength. These findings are consistent with previous literature that suggests both spontaneous and oscillatory power are altered in regular cannabis users (Edwards et al, 2009; Springer et al, 2021), and that cannabis use in PWH may have a neuroprotective effect, at least in some brain regions (Christopher-Hayes et al, 2021; Hall et al, 2021; Meade et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Finally, we also found that the association between the strength of spontaneous baseline activity and neural oscillations in the same spectral band was stronger in the dlPFC of cannabis users relative to nonusers, which may indicate that cannabis users are better able to compensate through increased oscillatory strength. These findings are consistent with previous literature that suggests both spontaneous and oscillatory power are altered in regular cannabis users (Edwards et al, 2009; Springer et al, 2021), and that cannabis use in PWH may have a neuroprotective effect, at least in some brain regions (Christopher-Hayes et al, 2021; Hall et al, 2021; Meade et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…compensate through increased oscillatory strength. These findings are consistent with previous literature that suggests both spontaneous and oscillatory power are altered in regular cannabis users (Edwards et al, 2009;Springer et al, 2021), and that cannabis use in PWH may have a neuroprotective effect, at least in some brain regions (Christopher-Hayes et al, 2021;Hall et al, 2021;Meade et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, our study did not assess oscillatory activity in the context of short-term drug effects, and such acute effects of cannabis are unlikely to generalize to our sample of chronic users who had not recently consumed such substances. Still other studies have identified alterations in chronic cannabis users in oscillatory activity related to attentional processing 45,46 . Compared to these studies however, the current study utilized a paradigm that did not utilize an attentional comparison.…”
Section: Discussionmentioning
confidence: 99%